2014
DOI: 10.1371/journal.pone.0103811
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis Peptides in the Exosomes of Patients with Active and Latent M. tuberculosis Infection Using MRM-MS

Abstract: The identification of easily measured, accurate diagnostic biomarkers for active tuberculosis (TB) will have a significant impact on global TB control efforts. Because of the host and pathogen complexities involved in TB pathogenesis, identifying a single biomarker that is adequately sensitive and specific continues to be a major hurdle. Our previous studies in models of TB demonstrated that exosomes, such as those released from infected macrophages, contain mycobacterial products, including many Mtb proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 34 publications
0
134
0
Order By: Relevance
“…Taken together, our results indicate the BMVs, not host-derived exosomes, are the EV population responsible for the trafficking of Mtb molecules from infected macrophages in vitro and for the regulation of uninfected immune cells. Interestingly, EVs (believed to be exosomes) that contain Mtb antigens have been isolated from the serum of patients with latent and active TB; several of these antigens have also been identified in Mtb BMVs (23, 35). This demonstrates that the release of EVs bearing Mtb components from Mtb-infected cells is physiologically relevant and occurs in the course of human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results indicate the BMVs, not host-derived exosomes, are the EV population responsible for the trafficking of Mtb molecules from infected macrophages in vitro and for the regulation of uninfected immune cells. Interestingly, EVs (believed to be exosomes) that contain Mtb antigens have been isolated from the serum of patients with latent and active TB; several of these antigens have also been identified in Mtb BMVs (23, 35). This demonstrates that the release of EVs bearing Mtb components from Mtb-infected cells is physiologically relevant and occurs in the course of human disease.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis produces BVs both during macrophage infection and in axenic culture; the BVs produced under these two conditions carry overlapping content (13, 1012) and similar immune-modulatory properties (3, 1214). The content and immune-modulatory properties of exosome preparations from infected macrophages (1, 5, 10) are also overlapping with BVs (11, 12, 15), although our interpretation is that this is due to the presence of BVs in the exosome preparations (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the first scenario, several studies have demonstrated that exosomes released from Mtb -infected cells contain mycobacterial products including proteins, RNAs and glycolipid141516. More importantly, our laboratory recently published the discovery of a panel of Mtb peptides that were identified in exosomes isolated from the sera of TB patients and LTBI individuals, confirming the fact that Mtb infection modifies exosome composition and could be a source of biomarkers for TB17.…”
mentioning
confidence: 60%
“…Exosomes are an important source of biomarkers for TB by virtue of the discovery of mycobacterial molecules packaged within these vesicles14151727. Here, the effect of the infection on host exosomal protein composition illustrates another potential opportunity to exploit exosomes as biomarkers of TB.…”
Section: Resultsmentioning
confidence: 99%